2003
DOI: 10.1038/sj.bjc.6601340
|View full text |Cite
|
Sign up to set email alerts
|

Opposing effects of dietary n-3 and n-6 fatty acids on mammary carcinogenesis: The Singapore Chinese Health Study

Abstract: We investigated the effects of individual fatty acids on breast cancer in a prospective study of 35 298 Singapore Chinese women aged 45 -74 years, who were enrolled during April 1993 to December 1998 (The Singapore Chinese Health Study). At recruitment, each study subject was administered, in-person, a validated, semiquantitative food frequency questionnaire consisting of 165 food and beverage items. As of December 31, 2000, 314 incident cases of breast cancer had occurred. We used the Cox regression methods t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
116
9
4

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(137 citation statements)
references
References 40 publications
8
116
9
4
Order By: Relevance
“…A total of 19 cohort or nested case-control studies have been conducted on the association between fat intake and breast cancer incidence (Table 1). [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Two of these studies considered premenopausal women separately 17,24 and 6 studies considered postmenopausal women separately. 16,17,22,23,26,27 Overall fat intake was not related to the incidence of breast cancer.…”
Section: Fat Intakementioning
confidence: 99%
See 1 more Smart Citation
“…A total of 19 cohort or nested case-control studies have been conducted on the association between fat intake and breast cancer incidence (Table 1). [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Two of these studies considered premenopausal women separately 17,24 and 6 studies considered postmenopausal women separately. 16,17,22,23,26,27 Overall fat intake was not related to the incidence of breast cancer.…”
Section: Fat Intakementioning
confidence: 99%
“…If there were 2 or more reports from 1 cohort, we included the report with the most up-to-date analysis. For fat intake we included 19 cohort studies, [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] 1 meta-analysis, 29 and 1 pooled analysis. 30 The meta-analysis and the pooled analysis included several of the 19 cohorts identified in our review.…”
Section: Study Selectionmentioning
confidence: 99%
“…4 One of the studies in the review, a study by Holmes et al, 7 found a slightly increased risk of breast cancer associated with higher dietary marine n-3 fatty acids in a cohort study with 88,795 women. A more recent study by Gago-Dominguez 8 found a significantly reduced risk of breast cancer in those with a high consumption of fish and marine n-3 fatty acids in The Singapore Chinese Health Study, a prospective cohort study with 314 breast cancer cases. Similarly, a significant inverse association between fish intake and breast cancer risk has been observed in Japanese women (2,385 breast cancer cases, 19,013 in reference group, with odds ratio (OR) 0.75, 95% confidence interval (CI) 0.57-0.98).…”
mentioning
confidence: 99%
“…Emerging evidence suggests that the n-6͞n-3 fatty acid ratio, rather than the absolute levels of the two classes of PUFAs, is the principal factor in the antitumor effects of n-3 PUFAs (10)(11)(12). Experimental data show that the efficacy of n-3 PUFAs in suppressing cancer growth depends not only on the amount of n-3 PUFAs but also on background levels of n-6 PUFAs (14).…”
mentioning
confidence: 99%
“…Because eicosanoid precursors (i.e., AA and EPA) compete for the same metabolic enzymes [cyclooxygenase (COX) and lipoxygenase], the availability of AA and EPA and their ratio in cellular lipids determine the cell eicosanoid profile. Thus, it has been suggested that a balanced n-6͞n-3 ratio of body lipids is essential for normal growth and development and plays an important role in prevention as well as treatment of many clinical problems, including cancer (10)(11)(12)(13).…”
mentioning
confidence: 99%